Max Arthur Cohn's Serigraphs and the Progressive Legacy of the New Deal - (:unkn) unknown (My University, 2024)
Max Arthur Cohn (American, b. England 1903-1998) was among the first artists to create “serigraphs,” a type of silkscreen print that gained popularity in the 1940s in New York City. Cohn was a founding member of the Silk Screen Group which later became the National Serigraph Society. This thesis contextualizes Cohn’s serigraphs within the history of the medium’s development and the broader history of mid-twentieth century American art. I analyze how Cohn’s serigraphs made for demonstration democratized access to the medium, Cohn’s experimentation in serigraphy expressed the diversity of style encouraged by Popular Front, and Cohn’s serigraph prints and greeting cards were supported by interior designers who became a crucial market for serigraphs. Serigraphs were shaped by the progressive ideals of interwar America and are a key legacy of the New Deal Federal Arts Projects. Serigraphy was a medium ideal for individual expression with collective origins and a public audience.
Keywords: Federal Art Project; Max Arthur Cohn; New Deal; Printmaking; Serigraph; Silkscreen